Udział delegacji Stanów Zjednoczonych w moskiewskiej konferencji Rady Ministrów Spraw Zagranicznych w 1947 roku - Wasiewicz, Magdalena (Acta Universitatis Lodziensis. Folia Historica, 2007)
This article presents the activity of US Delegation during the Moscow Conference in the spring 1947. The Ambassador of the US in Moscow General Walter Bedell Smith had installed the American Delegation in an improvised office in the Embassy residence, Spaso House. All of the members of the Delegation had difficulty adjusting to Moscow habits of work through the night. The East-West negotiations in 1947 primarily concerned the future of Germany. The United Slates tried unsuccessfully to advance the prospects of Germany’s reunification and demilitarization. The Soviets were extremely negative and would agree to nothing. Therefore the US Secretary of State General Marshall met Stalin on April 15, 1947. The meeting took eighty-eight minutes. Stalin listened while Marshall gave a situation report on the afflictions of the world and the need for peace. But Stalin expressed the view that present disagreements resembled a family quarrel. The impression made by Stalin on General Marshall was certainly one of the main causes of The Marshall Plan. Moreover in Moscow neither the Americans nor the Soviets had any intentions of working towards a Peace Treaty with Germany and German reunification. Moscow was the end of a road, the finish of a grand attempt by American democracy to get along with Russian communism.